REALITAS KINERJA PEGAWAI BANK SYARIAH - Finatariani, Endah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Getting lots of customers is proof of good service. This was obtained from hard work, good service without stopping, hospitality in every service, smile at all times, perseverance and team solidity. That's all called performance. On this occasion, will be sought out matters relating to efforts to improve performance. The object of research is the BCA Bank Syariah Mangga Dua. The research method uses quantitative and regression analysis. Data obtained by distributing questionnaires, which are closed with a Likert scale. That can be stated, discipline is a factor that maintains proper work behavior so that it focuses on performance. While motivation is a machine that spurs performance. Both are in different domains, but part of the performance dimension. Keywords : Discipline, Motivation, Performance